Pemanfaatan Tailing Untuk Campuran Lapis Tipis Aspal Pasir (Latasir) pada Perkerasan Jalan - Neni Kusnianti (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
There are many types of Hot Mix Asphalt mixture for wearing course, one of them is sand sheet. Sand is one of natural aggregate which is needed for sand sheet mixture, nevertheless the use of natural sand will affected environment, and also in some places this kind of material is difficult to find or its quality is not conform with the defined specification. In some places such as Timika (Papua), a sand sized material, which is a waste product of gold and copper mining process from PT Freeport, namely Tailing is abundant. Until recently, Tailing never been used in road construction. This paper will explain the effect of variation of tailing addition in sand sheet mixture. The use of Tailing as road material will reduce the effect of this waste to environment.